Standardization Efforts of Digital Pathology in Europe - Marcial García Rojo; Christel Daniel; Thomas Schrader (Analytical Cellular Pathology)
Background: EURO-TELEPATH is a European COST Action IC0604. It started in 2007 and will end in November 2011. Its main objectives are evaluating and validating the common technological framework and communication standards required to access, transmit, and manage digital medical records by pathologists and other medical specialties in a networked environment.